2002
DOI: 10.1210/jc.87.6.2540
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Aromatase P450 in Leiomyoma Tissue Is Driven Primarily through Promoter I.4 of the Aromatase P450 Gene (CYP19)

Abstract: The CYP19 gene encoding aromatase P450 (estrogen synthetase) is expressed in several extragonadal sites and regulated in a tissue-specific fashion, which is achieved by alternative use of the seven different promoters (and corresponding exons 1) of the CYP19 gene. Previously, we demonstrated that aromatase P450 is overexpressed in leiomyoma tissue and that in situ estrogen synthesized in leiomyoma tissues possibly plays a role in leiomyoma growth. To elucidate the mechanism of overexpression of aromatase P450,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Promoters contain specific DNA sequences and response elements that provide an initial binding site for RNA polymerase and for the transcription factors that recruit RNA polymerase. In humans, six promoter regions have been identified in CYP19 genes namely: Ia, Ib, Ic, Id (II), Ie and If; these regions work in the placenta, foetal liver and skin fibroblast, ovary, ovary and testis, placenta and brain, respectively (Mahendroo et al , ; Shozu & Simpson, ; Shozu et al , ). The gonad‐specific promoter is conserved in humans, bovines and avians (Jenkins et al , ; Honda et al , ).…”
Section: Primers Used For Carassius Auratus Gene Cloning and The Exprmentioning
confidence: 99%
“…Promoters contain specific DNA sequences and response elements that provide an initial binding site for RNA polymerase and for the transcription factors that recruit RNA polymerase. In humans, six promoter regions have been identified in CYP19 genes namely: Ia, Ib, Ic, Id (II), Ie and If; these regions work in the placenta, foetal liver and skin fibroblast, ovary, ovary and testis, placenta and brain, respectively (Mahendroo et al , ; Shozu & Simpson, ; Shozu et al , ). The gonad‐specific promoter is conserved in humans, bovines and avians (Jenkins et al , ; Honda et al , ).…”
Section: Primers Used For Carassius Auratus Gene Cloning and The Exprmentioning
confidence: 99%
“…The human aromatase gene was mapped to chromosome 15, band q21 by in situ hybridization studies and was confirmed by recent human genome analysis . The gene consists of nine coding exons.…”
Section: Regulation Of Aromatase Expression In Endometriosismentioning
confidence: 81%
“…In uterine leiomyoma, aromatase is present at a higher level compared to adjacent normal myometrium and could play a role in leiomyoma growth wreviewed by Shozu et al (61)x. In uterine leiomyoma, aromatase is present at a higher level compared to adjacent normal myometrium and could play a role in leiomyoma growth wreviewed by Shozu et al (61)x.…”
Section: Discussionmentioning
confidence: 99%